MANAJEMEN PEMBINAAN SEKOLAH SEPAKBOLA (SSB) BINA BANGSA BANDAR LAMPUNG - Luthfi Zahir; Rahmat Hermawan; Lungit Wicaksono (Journal Physical Education, Health and Recreation, 2018)
Various issues in coaching football at the Bina Banga Soccer School (SSB) include the implementation of coaching, management of management, and the purpose of coaching. SSB Bina Bangsa is a place of football in the city of Bandar Lampung that has good consistency in efforts to foster football achievements and have good achievements at the district and provincial levels, even with infrastructure and makeshift organizations. The main problem under study was the management of the Bina Bangsa Bandar Lampung Football School (SSB), because this SSB had not yet received an achievement at the National level championship. This study aims to reveal the various problems that exist in the Bina Bangsa Bandar Lampung Football School (SSB). To answer this problem, the approach used is descriptive qualitative method. Data collection techniques using interview methods, observation methods, questionnaires and documentation methods. Data validity with triangulation techniques. Data analysis with data collection, data reduction, data presentation, and conclusion drawing. rom the results of the study the data was collected and concluded so as to obtain results, 1) The management conditions at Bina Bangsa SSB have run smoothly, in managing the Bina Bangsa SSB organization run rudely, because there are still many obstacles, lack of support from the local government to help with the Football School financial problems. 2) The implementation of the coaching program at Bina Bangsa SSB uses the Chemo theory development pattern, which starts from the grafting, nursery and performance improvement carried out by SSB Bina Bangsa. 3) The achievement of Bina Bangsa SSB can be said to be good enough in Lampung Province. Achievements at the district and provincial levels have been felt.